UMP research works received recognition in the US - UMP, PNC
Universiti Malaysia Pahang (UMP) won big in the US when four of its researchers brought home four gold medals and a special award following their successful feats at the ‘Invention and New Product Exposition’ (INPEX 2013) held at Monroeville Convention Centre, Pittsburgh, US.